Application of the Prompting Technique to Increase the Frequency of Eye Contact in Autism Spectrum Disorder (ASD) - Misdayani Misdayani; Budi Susetyo (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine whether there is influence or not from the prompting technique to improve the ability to make eye contact in children with autism spectrum disorders in interacting and communicating with others. The research method used in this study is a mixed method or combination (mixed method) which combines quantitative data with qualitative data. The research subject was one student who was a child with an autistic spectrum disorder at SLB Agro Industry Bandung. There are three prompts applied in this study, namely verbal prompts, gestural prompts and physical prompts. The application of this technique is accompanied by extrastimulus and positive reinforcement. Prompting is carried out in the least-to-most procedure with the aim of providing assistance from the weakest first. This means that if the subject can make eye contact with the weakest prompt, then the next prompt does not need to be given. Data was obtained through direct observation recording of each treatment session carried out. The data obtained is depicted in a graph showing changes and improvements from the initial treatment given to the last treatment. The results showed that there was an increase in the frequency of making eye contact when prompting was given. Even so, eye contact did not appear consistently every time the subject was called by name, but it was consistent enough when it was done using prompting techniques with gestural prompts and giving extra stimuli in the form of toys and the subject's favorite food.